Indústria cultural e educação: caminhos de volta - Ludwig, Cristiane (2007)
This research was presented to the Pos Graduation Program in Education, specifically to the Master Degree level, in the Centro de Educação (Center of Education) at UFSM (Federal University of Santa Maria), for the line of research on Education and Art. The approach of this work is about the relations between education and cultural industry and their implications in the actual context starting from the diagnosis of the dialectic to the convenient cultural formation while pseudo culture, by Theodor W. Adorno, and of the action communicative theory, by Jürgen Habermas, who emphasizes the public space transformation. The purpose is analyses the concept of cultural industry as a mechanism of aesthetization to the experienced world. In the sense to aid the reversion to the cultural processes of appropriation, it makes use of the hermeneutic reconstructive dialog proposing some outlook for education in order that human being can dialogue and interact with the challenges that results from this context. In this way, this research proposes the work to decode images as a tool to think in better strategies for the formation of civic judgment. The discussion hypothesis proposes the idea that pedagogical changes which can contribute to destabilize the unidimensionality given to the communication, by the distorted practice, must pass by reeducation to the meaning of comprehend. This approach allows other comprehension meanings opening, immersed in the expressed messages, once presupposes participation in a community governed by communicative action, that it contemplates a way of double hand and that itinerary of has not only gone, but also ways in return. Thus the educative practice, through the ontextualized interventions in the experienced world, opens other ways of comprehension to the meanings plurality that emerge form the cultural patrimony, mainly the recognize of the other alterity and the differences, considering the complexity of the daily emergent values from the new interactive media.